Plastic Pollution Patterns in Offshore, Nearshore and Estuarine Waters: A Case Study from Perth, Western Australia - Hajbane, Sara; Pattiaratchi, Charitha B. (Frontiers in Marine Science, 2017)
Plastic pollution in marine surface waters is prone to high spatial and temporal variability. As a result increases in pollution over time are hard to detect. Selecting areas, based on variable oceanographic and climatological drivers, rather than distance-based approaches, is proposed as a means to better understand the dynamics of this confounding variability in coastal environments. A pilot study conducted in Perth metropolitan waters aimed to explore the applicability of this approach, whilst quantifying levels of plastic pollution in an understudied part of the world. Pollution ranged from 950 to 60,000 pieces km-2 and was dominated by fishing line. Offshore concentrations were highest with strongest Leeuwin Current flow in the estuary immediately after rainfall, and increased in the nearshore after estuarine outfall. Results elucidated significant relationships between physical drivers and concentration changes and therefore their roles in increasing or decreasing local plastic pollution. Such observations can form the basis for predicting peak pollution periods and inform targeted mitigation.